2022
DOI: 10.1093/pm/pnac103
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Neurotomy Does Not Cause Fatty Degeneration of the Lumbar Paraspinal Musculature in Patients with Chronic Lumbar Pain—A Retrospective 3D-Computer-Assisted MRI Analysis Using iSix Software

Abstract: Structured Abstract Objective The present study aimed 1) to analyze the relative paraspinal autochthonous intramuscular fat volume before and after radiofrequency neurotomy (RFN), and 2) to compare it to the contralateral non-treated side. Design Retrospective cohort study. Setting Inselspital, University Hospital Bern, Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[ 44 ], and a significant loss of paravertebral muscles, requiring stabilization, was observed after cervical MB radiofrequency denervation [ 45 ]. On the contrary, recently published articles did not confirm these findings [ 46 ]. This conflicting evidence seems related to the use of different methods to measure muscular atrophy and does not consider possible catabolic effects of injected steroids on muscle tissue [ 47 ].…”
Section: Discussionmentioning
confidence: 77%
“…[ 44 ], and a significant loss of paravertebral muscles, requiring stabilization, was observed after cervical MB radiofrequency denervation [ 45 ]. On the contrary, recently published articles did not confirm these findings [ 46 ]. This conflicting evidence seems related to the use of different methods to measure muscular atrophy and does not consider possible catabolic effects of injected steroids on muscle tissue [ 47 ].…”
Section: Discussionmentioning
confidence: 77%
“…48 Recently, RFA has also been proven to preserve the surrounding muscles well. Oswald et al 57 retrospectively reviewed symptomatic facet joint pain patients treated with RFA. They used magnetic resonance imaging analysis to compare the lumbar paraspinal musculature before and at least 6 months after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Another retrospective study (n = 20) found no differences in the paraspinal intramuscular adipose tissue volume and distribution before and after RFN. 115 An analysis of aforementioned studies on behalf of the Spine Intervention Society Patient Safety Committee concluded that despite inconclusive evidence for multifidus atrophy after MBB radiofrequency, some degree of atrophy is plausible but requires further study. 116…”
Section: Com Pl Icat Ion Smentioning
confidence: 99%